Diseño y construcción de un sistema de biorreactores de inmersión temporal neumática para la multiplicación de ananas comosus var. roja trujillana - Solórzano Acosta, Richard Andi (2016)
The problems to lay plans and to construct a biorreactor of temporary immersion that be of low cost and with equal or better efficiency exist than the commercial prototypes. To acquire them motives are what this technology at developing countries has not taken effect for in the foreign market and his high cost. The present work attempts initially identifying the designing parameters of one twin-jet of temporary immersion stops next climbing a complete system of 24 tanks, next implementing the system of automatization pneumatic electro and accomplishing an efficiency test in the multiplication in Ananas's vitro comosus var roja trujillana. That way one laid plans and the L constructed biorrreactores's system of temporary pneumatic immersion of low cost with 24 tanks of 2 each one. One laid plans and a circuit implemented the automatization of biorrreactores's system of temporary pneumatic intervening immersion timer whose designing parameters matched : Duration of the process of propagation, which depends on the period of multiplication of cultivation and a sincere variable is that means that the laborer makes a decision when putting out the system; The duration out of every immersion, which on the grounds of complexity of the algorithm standardized itself like 1 minute; Frequency of immersion, which programmed itself for intervals of 1.2.3.4.5.6.7.8 hours respectively and duration of aeration, which as from a performance testing elected times themselves of 0.20.30.40.50.60.70, and 80 seconds that correspond at the same time in the course of time of delivery of compressed air; Additionally determined him Ananas's rate of multiplication comosus var. truxilian red in the system of immersion which went from 6,5 times for propagative inoculated unit in thirty days. One comes to an end than the system increased of biorreactores of temporary pneumatic automated immersion designed and constructed works according to the designing parameters and gets an appropriate rate of multiplication for the propagation of the cultivation of the roja trujillana pineapple.